The issues and challenges of implementation of zakat distribution to the poor and needy by Lembaga Zakat Negeri Kedah (LZNK) / Muhammad Fauzan Ruslan - Ruslan, Muhammad Fauzan (2025)
This study investigates issues and challenges in the implementation of zakat distribution to the poor and needy by the Kedah State Zakat Board (LZNK). It aims to provide a comprehensive understanding of the mechanism of zakat distribution, focusing on how funds are collected, managed and allocated to recipients. By examining the operational framework of LZNK, the researcher identified problem statement in practice in zakat management in Kedah as the inefficiency of the bureaucracy within the Kedah State Zakat Board (LZNK), which hinders the timely and effective distribution of zakat to the poor and needy. The researcher used qualitative methods, including interviews to gather perspectives from the Kedah State Zakat Board (LZNK). This method enables an in-depth study of the socio-economic factors that affect the distribution of zakat, as well as the specific challenges faced by amil (zakat managers). The results of this study revealed related to significant obstacles, such as bureaucratic inefficiency, lack of awareness among zakat recipients, and public perception issues that hinder effective zakat distribution. This study emphasizes the need to improve strategies to increase the efficiency and effectiveness of zakat distribution. Best practices include leveraging technology for better outreach, increasing transparency in fund management and fostering community engagement. By addressing these challenges, this research can contribute to the ongoing discourse on the role of zakat in poverty alleviation and social justice and further increase its impact as a tool for social welfare in Kedah.